2007
DOI: 10.1080/15459620701691023
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos Release from Whole-Building Demolition of Buildings with Asbestos-Containing Material

Abstract: The whole-building demolition method, which entails one-or two-story buildings pushed down by heavy equipment, loaded into trucks, and hauled away, is generally the most cost-effective means to remove small buildings. For taller buildings, a crane and wrecking ball may be used initially to reduce the height of the building. Demolitions might release asbestos fibers from friable asbestos-containing material (ACM). Fibers also might be released from nominally nonfriable ACM (Categories I and II nonfriable ACM) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 3 publications
0
12
1
Order By: Relevance
“…Brown (1987) reported that mean asbestos concentrations during renovation and demolition of asbestos-cement clad building were 0.3 to 0.6 f/ml for roofs and less than 0.1 f/ml for walls, which are higher than the amounts were found in this study. In the current study, the average concentration was 0.2 SEM f/ml (0.07 PCM f/ml), which is considerably lower than the levels of asbestos reported in some of the previous studies 5 , 18 ) . It is interesting to note that, the SEM results were higher than the PCM results for all the personal samples.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Brown (1987) reported that mean asbestos concentrations during renovation and demolition of asbestos-cement clad building were 0.3 to 0.6 f/ml for roofs and less than 0.1 f/ml for walls, which are higher than the amounts were found in this study. In the current study, the average concentration was 0.2 SEM f/ml (0.07 PCM f/ml), which is considerably lower than the levels of asbestos reported in some of the previous studies 5 , 18 ) . It is interesting to note that, the SEM results were higher than the PCM results for all the personal samples.…”
Section: Discussioncontrasting
confidence: 81%
“…Tang tong (2008) reported that construction workers may have been exposed to concentrations of airborne asbestos approximately 4 times higher than the OSHA PEL of 0.1 f/ml 4 ) . Other reported measurements of asbestos fibers during the demolition of roofing were 0.6 f/ml 5 ) . During recent decade, some courtiers have banned using all types of asbestos 6 , 7 ) .…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…More importantly, it allowed detection of non-friable asbestos contaminated material potentially not detected with a whole soil milling process. We refer to the class of asbestos containing material that cannot be crumbled, pulverized, or reduced to powder by pressure (Perkins et al 2007). Currently, EPA is evaluating this sampling method for its applicability to Superfund site characterization.…”
Section: Resultsmentioning
confidence: 99%
“…Most at risk, in this case, is the health of demolition workers and the general public [ 27 ]. The EPA’s National Emission Standards for Hazardous Air Pollutants (NESHAP), the Occupational Safety and Health Act (2009), and the Asbestos Safety Management Act (2012) state that all ACM must be removed from buildings in advance of demolition [ 28 , 29 ]. Therefore, the building demolition process generates GHG emissions two-fold—first by the precursory step of ACM removal, and second, by the demolition itself.…”
Section: Introductionmentioning
confidence: 99%